Overcoming life's sorrows : learning from Jeremiah - Lessing, R. Reed (Robert Reed), 1959- (St. Louis : Concordia Publishing House, 2021)
"This unique book is a combination of Bible commentary and devotional reflection, applying biblical truth to our lives and inviting readers to see how God uses His people's story in the Book of Jeremiah to speak to our difficult questions in the face of disaster. Anyone who has experienced a life-altering event will benefit from this resource"--
Meet Jeremiah -- Overcoming through God's word -- Overcoming through confession and absolution -- Overcoming through hope -- Overcoming through worship -- Overcoming through expressing grief -- Overcoming through renouncing idolatry -- Overcoming through laments -- Overcoming through God's tests -- Overcoming through listening -- Overcoming through trust -- Overcoming through humility -- Overcoming through God's grace -- Overcoming through the Good Shepherd -- Overcoming through seeing -- Overcoming through persistence -- Overcoming through surrender -- Overcoming through shalom -- Overcoming through the new David -- Overcoming through the renewed covenant -- Overcoming through taking risks -- Overcoming through tenacity -- Overcoming through the storm -- Overcoming through faith -- Overcoming through singing -- Who overcomes?
Description based on print version record and CIP data provided by publisher.
Keywords: Bible. -- Devotional literature; Bible. -- Commentaries; Life change events -- Religious aspects -- Christianity; Commentaries